Antifungal metabolites from the rhizospheric Penicillium sp. YIM PH 30003 associated with Panax notoginseng. (March 2015) - Yang, Yabin; Yang, Fangfang; Miao, Cuiping; Liu, Kai; Li, Qiling; Qin, Shaohuan; Zhao, Lixing; Ding, Zhongtao
Graphical abstract: Highlights: Four new compounds were isolated from Penicillium sp. YIM PH30003. Compounds1 –4 might share the similar biosynthetic pathway with pistillarin. Compounds1 –10 showed antifungal activities against Fusarium solani . Abstract: Two new N-benzoylamino acids, peniginseng A-B (1 –2 ), and two new fatty acids, peniciginseng A-B (5 –6 ), were isolated during the fermentation of Penicillium sp. YIM PH30003, an endophytic fungus associated with Panax notoginseng (Burk.) F.H. Chen. Their structures were assigned based on a combination of 1D and 2D NMR and mass spectral data. The N-benzoylamino acids (1 –4 ) might share similar biosynthetic pathways with the rare siderophore pistillarin. Compounds1 –10 showed antifungal activities (MICs 16–128 μg/mL) against Fusarium solani, the pathogenic fungus of P. notoginseng .